(untitled) (Research, Society and Development, 2023)
This study sought to verify the presence of the Impostor Phenomenon (IF) in female professors at a public university in southern Brazil, which is when women attribute their success to luck or another factor, but not to their ability to get where they are. An inferential statistical analysis was carried out and the results reveal that the older the age, the less impostors these teachers consider themselves to be. In parallel, the longer the length of service at the university, the smaller the presence of the IF. The qualification does not interfere with the greater or lesser presence of the IF, as well as being in a leadership position. Although the literature shows that women who work in areas predominantly occupied by men have a greater presence of the phenomenon, in this study this is not evident. IF is contemporary and widespread, whether to a greater or lesser extent. The data obtained in this study indicate that some of these teachers need to believe in themselves more, developing their self-esteem more. The university needs to collaborate in this, developing actions that overcome “tokenism” in order to alleviate the scenario found, which oppresses and sickens. The ambivalence of being successful and not enjoying it needs to change.